DO REVERSE STOCK SPLITS PREDICT BANKRUPTCY? CASE OF INDONESIA LISTED FIRMS - Swarnadwipa, Felix
Reverse stock split is an activity of converting larger amount of shares into smaller amount, at consequence of rising stock price with equal ratio division of shares. Based on past researchers, there are arguments that shows positive returns and negative returns, creating a confusion for investors to act regarding their investment on reverse stock split firms. The researcher tries to provide the solution by analyzing the financial distress of the firm, by using the most accurate financial distress predictor on Indonesia public listed firms at average industries, which is Grover model. Therefore, this study aims to investigate whether firms that announce reverse stock split tend to have financial distress or not. There will be three times research event examination, which are one year, two years, and three years after reverse stock split occurred. Through this paper, a total of 30 samples are used, consisting of 15 reverse stock split firms and 15 non-reverse stock split firms that are listed and traded for a period year of 2010 to 2019. Our findings show that Earnings Before Interest and Taxes per Total Assets (EBITTA) is a significant predictor in predicting financial distress on one year, two years, and three years prediction after reverse stock split happened. Firms with higher EBITTA value are found to have less financial distress risk. There are also other significant financial ratios for predicting financial distress based on each time event. Finally, this study provides comprehensive and new insight to investors that it is preferable to invest in low financial distress firms through identifying firms that have high EBITTA for one year until three year in the future after reverse stock split event of the firm.